Loyalty, Satisfaction, and Performance: Do We Really Need Training as a Mediator? - Supriyanto; Abd. Kodir Djaelani; Abdul Wahid Mahsuni (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to examine the influence of loyalty and job satisfaction on employee performance and to analyze the mediating role of human resource training at CV Putra Mahkota. Using a quantitative explanatory design, all 65 employees were surveyed through questionnaires and the data were analyzed using SEM-PLS. The findings show that loyalty and job satisfaction positively and significantly affect both employee performance and human resource training, and that training itself significantly improves performance. However, human resource training does not mediate the effects of loyalty or job satisfaction on performance. These results imply that organizations should strengthen direct strategies to enhance employee loyalty and job satisfaction, while improving training programs to ensure they are more structured, continuous, and aligned with performance needs, offering valuable direction for future research and managerial practice.